The effects of second-generation antipsychotics in borderline personality disorder - a systematic review. - Baltazar Gabriel Moreira de Oliveira (2021)
Borderline personality disorder (BPD) is a convoluted psychiatric disease that requires a considerable amount of health resources to be adequately treated. Previous studies have shown that pharmacotherapy can be advantageous for BPD. Within the drugs tested, second-generation antipsychotics (SGAs) showed a more consistent positive effect in patients with BPD. However, the amount of evidence available at the time was insufficient to justify its recommendation. The aim of this systematic review is to qualitatively assess the randomized controlled trials (RCTs) of SGAs in BPD patients currently available. Database searches were performed using MEDLINE, SCOPUS, ISI Web of Knowledge and PsycInfo. Study selection and data collection were carried out independently by two researchers. Out of 1294 records (without duplicates), nine studies were included in this review. The results confirm the findings of a previous review. Most SGAs show a significant decrease in various BPD symptoms in comparison to placebo. However, there was only one new study compared to the last review. Current findings suggest SGAs are effective against BPD and can serve as adjuvant therapy. Further RCTs are needed with larger samples and with several intervention arms.